Long Distance Runners in the Marine Realm: New Insights Into Genetic Diversity, Kin Relationships and Social Fidelity of Indian Ocean Male Sperm Whales - Girardet, Justine; Sarano, Francois; Richard, Gaëtan; Tixier, Paul; Guinet, Christophe; Alexander, Alana; Sarano, Véronique; Vitry, Hugues; Preud’homme, Axel; Heuzey, René; Garcia-Cegarra, Ana M.; Adam, Olivier; et al. (Frontiers in Marine Science, 2022)
Adult male sperm whales (Physeter macrocephalus) are long distance runners of the marine realm, feeding in high latitudes and mating in tropical and subtropical waters where stable social groups of females and immatures live. Several areas of uncertainty still limit our understanding of their social and breeding behavior, in particular concerning the potential existence of geographical and/or social fidelities. In this study, using underwater observation and sloughed-skin sampling, we looked for male social fidelity to a specific matrilineal sperm whale group near Mauritius. In addition, we captured a wider picture of kin relationships and genetic diversity of male sperm whales in the Indian Ocean thanks to biopsies of eight individuals taken in a feeding ground near the Kerguelen and Crozet Archipelagos (Southern Indian Ocean). Twenty-six adult male sperm whales were identified when socializing with adult females and immatures off Mauritius. Sloughed-skin samples were taken from thirteen of them for genetic analysis. Long-term underwater observation recorded several noteworthy social interactions between adult males and adult females and/or immatures. We identified seven possible male recaptures over different years (three by direct observation, and four at the gametic level), which supports a certain level of male social fidelity. Two probable first- and thirty second-degree kin relationships were highlighted between members of the social unit and adult males, confirming that some of the adult males observed in Mauritian waters are reproductive. Male social philopatry to their natal group can be excluded, as none of the males sampled shared the haplotype characteristic of the matrilineal social group. Mitochondrial DNA control region haplotype and nucleotide diversities calculated over the 21 total male sperm whales sampled were similar to values found by others in the Indian Ocean. Our study strongly supports the existence of some levels of male sperm whale social fidelity, not directed to their social group of birth, in the Indian Ocean. Males sampled in breeding and feeding grounds are linked by kin relationships. Our results support a model of male mediated gene flow occurring at the level of the whole Indian Ocean, likely interconnected with large-scale geographical fidelity to ocean basin, and a small-scale social fidelity to matrilineal social groups.